2019
DOI: 10.1002/ppsc.201900323
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Surface Facets of Gold Nanorods in Wet‐Coated Thin Films with Grazing‐Incidence Wide Angle X‐Ray Scattering

Abstract: This work studies the surface facets of gold nanorods (AuNRs) in wet‐coated nanoparticle thin films with synchrotron‐light‐based grazing‐incidence wide angle X‐ray scattering (GIWAXS), which provides statistically relevant results on many nanoparticles. Air‐brush spraying deposits the monodisperse AuNRs into sparse monolayers where the long axis of rods is parallel to the substrate surface. It is found that the crystalline facets of individual AuNRs in the sparse monolayer are all in the same orientation, as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…A λ 750 K detector was employed to collect the 2D GIWAXS patterns. 59,60 The sample-todetector distance was 115 ± 1 mm, calibrated with cerium dioxide.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…A λ 750 K detector was employed to collect the 2D GIWAXS patterns. 59,60 The sample-todetector distance was 115 ± 1 mm, calibrated with cerium dioxide.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The α i was slightly above the critical angle for total reflection (α c ) of conjugated polymers used in this work but below α c of silicon substrate. A λ 750 K detector was employed to collect the 2D GIWAXS patterns. , The sample-to-detector distance was 115 ± 1 mm, calibrated with cerium dioxide.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…the Supporting Information). GIWAXS is a well-established protocol to characterize the surface and interface structures of polymer thin film, , including PEDOT:PSS before and after IL doping. For example, Kee et al demonstrated a highly ordered nanofibrillar structures of PEDOT, and Saxena et al reported a shortened π–π stacking distance between PEDOT molecules upon salts’ doping.…”
mentioning
confidence: 99%
“…While SEM yields topographical and surface morphology characterization, the strong uniaxial crystallographic anisotropy of the hexaferrite phase (P6 3 /mmc) and single-crystalline nature of the platelets require determining their orientation using diffraction methods, especially for the thicker films. Hence, GIWAXS was employed to quantify the orientations of nanoplatelets in the deposited films 58 (Figures Those distributions differ significantly for NAL and SHF thin films and evolve with the number of layers of hexaferrite particles (Figures 3b,c, S7 and Table S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…While SEM yields topographical and surface morphology characterization, the strong uniaxial crystallographic anisotropy of the hexaferrite phase ( P 6 3 / mmc ) and single-crystalline nature of the platelets require determining their orientation using diffraction methods, especially for the thicker films. Hence, GIWAXS was employed to quantify the orientations of nanoplatelets in the deposited films (Figures a and S5). A typical 2D GIWAXS pattern indicates a uniaxial SrFe 12 O 19 texture in the films, with the set of maxima corresponding to the in-plane orientation of the MNPs with the [00l] direction normal to the film surface.…”
Section: Resultsmentioning
confidence: 99%